A comparison between PLGA-PEG and NIPAAm-MAA nanocarriers in curcumin delivery for hTERT silencing in lung cancer cell line - Roointan, A; Sharifi-Rad, M; Badrzadeh, F; Sharifi-Rad, J (Cellular and Molecular Biology, 2016)
Lung cancer is the most common cancer among men. Since the main reason of cancer cells immortality is telomerase activity, targeting of such enzyme can be a promising approach in cancer therapy. Curcumin is a safe and efficient anticancer agent in this context, but its applications in cancer therapy are limited because of its hydrophobic structure and low solubility in water. Today, using nanocarriers for delivery of such anticancer agents is a well performed method. Here, we developed and compared the efficiency of two nanocarriers (PLGA-PEG and NIPAAm-MAA) in delivery of curcumin and also in levels of hTERT silencing in lung cancer cell line (calu-6). Scanning electron microscopy, MTT assays and real-time PCR were used for imaging, cytotoxicity testing and measuring the expression levels of hTERT after treatment of cells with different concentrations of free curcumin and curcumin loaded nanocarriers. The MTT results demonstrated that the IC50 values of curcumin loaded nanocarriers were in lower concentrations than free curcumin. The hTERT expression levels were decreased by curcumin loaded PLGA-PEG more than curcumin loaded NIPAAm-MAA and free curcumin. Our results showed that the curcumin loaded PLGA-PEG can be a useful nano based carrier for delivery of anti-cancer agents such as curcumin to fight lung cancer.